Spirituality of the Traumatized Child: A Call for Increased Faith Community Participation in the Trauma-Healing Process for Children - Westerfield, Caitlin M. (Journal of religion and health, 2022)
One-third of all children worldwide experience trauma. This includes domestic violence, serious illness, physical or mental abuse, and death of a parent, among other traumatic experiences. Children who experience trauma are more likely to experience other mental health disorders and often reject the religious and spiritual institutions of their upbringing. While cognitive-based therapy and other traditional psychological methods are crucial to the care of these children, incorporating their spirituality can be a helpful adjunct for their healing. Further, religious communities can play a critical role in reintroducing healthy forms of relationship building and community attentiveness, while providing a safe environment for coping.